2018
DOI: 10.1038/s41586-018-0570-8
|View full text |Cite|
|
Sign up to set email alerts
|

Trans-differentiation of outer hair cells into inner hair cells in the absence of INSM1

Abstract: The mammalian cochlea contains two types of mechanosensory hair cells (HCs) that play different and critical roles in hearing. Inner hair cells (IHCs), with an elaborate presynaptic apparatus, signal to cochlear neurons and communicate sound information to the brain. Outer hair cells (OHCs) mechanically amplify sound-induced vibrations, enabling enhanced sensitivity to sound and sharp tuning. Cochlear HCs are solely generated during development and their death, most often of OHCs, is the main cause of deafness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 40 publications
8
94
0
Order By: Relevance
“…In contrast, no puncta were observed in hair cells or supporting cells at either time point. Next, we used the gEAR portal to query four recently published RNAseq datasets (Cai et al, 2015;Elkon et al, 2015;Li et al, 2018;Wiwatpanit et al, 2018) in which hair cells had been isolated at P0 or from adults using fluorescence activated cell sorting (FACS) or visual collection. For comparison, the expression levels of three known hair-cell-specific genes (Pou4f3, Gfi1, Myo7a) were compared with Pou4f1.…”
Section: Pou4f1 Is Not Expressed In Hair Cells or Supporting Cellsmentioning
confidence: 99%
“…In contrast, no puncta were observed in hair cells or supporting cells at either time point. Next, we used the gEAR portal to query four recently published RNAseq datasets (Cai et al, 2015;Elkon et al, 2015;Li et al, 2018;Wiwatpanit et al, 2018) in which hair cells had been isolated at P0 or from adults using fluorescence activated cell sorting (FACS) or visual collection. For comparison, the expression levels of three known hair-cell-specific genes (Pou4f3, Gfi1, Myo7a) were compared with Pou4f1.…”
Section: Pou4f1 Is Not Expressed In Hair Cells or Supporting Cellsmentioning
confidence: 99%
“…Last, we performed multiplex in situ hybridization and found that ectopic Fgf8 + IHCs lacked expression of Insm1 (Fig. 3D), which is required for driving an OHC identity (25). Together, these results suggest ectopic formation of IHCs at the expense of OHCs in the lateral compartment before E18.5.…”
Section: Resultsmentioning
confidence: 78%
“…The gene is expressed only in nascent OHCs and in its absence, the OHCs transdifferentiate into IHCs. Using Ism1 to sort OHC from IHC populations, the authors identified several additional genes that were specific to IHCs vs OHCs . To differentiate IHCs from OHCs, we note the presence of Insm1 in OHCs in the GRN.…”
Section: Hair Cell Transcription Factorsmentioning
confidence: 99%